Vertebrobasilar artery cooling infusion in acute ischemic stroke for posterior circulation following thrombectomy: Rationale, design and protocol for a prospective randomized controlled trial - Cheng, Zhe; Ding, Yuchuan; Rajah, Gary B.; Gao, Jie; Li, Fenghai; Ma, Linlin; Geng, Xiaokun (Frontiers in Neuroscience, 2023)
Background Although endovascular mechanical thrombectomy demonstrates clinical efficacy in posterior circulation acute ischemic stroke (AIS), only one third of these patients attain functional independence with a third of patients’ expiring despite vascular recanalization. Neuroprotection strategies, such as therapeutic hypothermia (TH) have been considered a promising adjunctive treatment in AIS. We propose the following rationale, design and protocol for a prospective randomized controlled trial (RCT) aimed to determine whether Vertebrobasilar Artery Cooling Infusion (VACI) improves functional outcomes in posterior circulation AIS patients post mechanical thrombectomy. Methods Subjects in the study will be assigned randomly to either the cooling infusion or the control group in a 1:1 ratio (n = 40). Patients allocated to the cooling infusion group will receive 300 ml cool saline at 4C through the catheter (30 ml/min) into vertebral artery after thrombectomy. The control group will receive the same volume of 37C saline. All patients enrolled will receive standard care according to current guidelines for stroke management. The primary outcome is symptomatic intracranial hemorrhage (ICH), whereas the secondary outcomes include functional outcome score, infarction volume, mortality, ICH, fatal ICH, cerebral vasospasm, coagulation abnormality, pneumonia and urinary infection. Discussions This study will determine the preliminary safety, feasibility, and neuroprotective benefits of VACI in posterior circulation AIS patients with reperfusion therapy. The results of this study may provide evidence for VACI as a new therapy in posterior circulation AIS. Clinical Trial Registration: www.chictr.org.cn, ChiCTR2200065806, registered on November 15, 2022.